The Nexus between Leadership Hygiene Practices of School Leaders and Teachers Instructional Effectiveness - Oksok, Naome (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the nexus between leadership hygiene practices of school leaders and teacher instructional effectiveness in public secondary schools in Polanco I and Polanco II Districts, Division of Zamboanga del Norte, during School Year 2025–2026. Anchored primarily on Herzberg’s Two-Factor Theory, and supported by Instructional Leadership Theory, Transformational Leadership Theory, the Job Demands–Resources Model, and Leader–Member Exchange Theory, the study investigated how foundational leadership conditions influence teachers’ performance in key instructional domains. A quantitative-correlational, descriptive-survey design was employed. Data were gathered through an adopted and validated questionnaire based on Herzberg’s Motivation-Hygiene Theory, using a five-point Likert scale. The respondents consisted of 176 participants, including principals, head teachers, and teachers from six public secondary schools. Descriptive statistics and inferential statistics, including mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis, were used in data analysis. Findings revealed that school leaders’ hygiene practices were rated at a very high extent across all dimensions, particularly in professional relationships, collegial respect, accountability, and consistency in administrative decisions. Teachers’ instructional effectiveness was likewise rated very high in instructional planning and organization, pedagogical competence, classroom management, learner engagement, assessment literacy, and professional reflection. Correlational findings showed that clarity and fairness of policies, transparent communication, supportive supervision, collegial respect, and accountability and consistency in decisions had significant moderate positive relationships with teacher instructional effectiveness, while equitable task distribution and workload management showed no significant relationship. The study concludes that leadership hygiene practices are essential organizational conditions that strengthen teacher effectiveness and instructional quality. It recommends that school leaders continuously institutionalize fair policies, transparent communication, supportive supervision, and accountable administrative practices. The study aligns most directly with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions). Its sustainability impact lies in supporting educational, institutional, and governance sustainability through leadership conditions that promote teacher engagement, stable school operations, and improved learning outcomes.
Keywords: Accountability; Instructional Effectiveness; Leadership Hygiene Practices; Pedagogical Competence; Professional Reflection; School Leaders; Teacher Performance; Transparent Communication